2012
DOI: 10.1007/s12149-012-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sequential FDG-PET/CT for monitoring bone metastasis of breast cancer during therapy: correlation between morphological and metabolic changes with tumor markers

Abstract: Changes of FDG uptake are useful for evaluating individual bone metastases in cases of breast cancer during therapy. Lytic change on CT images suggests progression of bone metastasis. The lysis-progression/sclerosis-improvement pattern was observed in the majority of subjects, but a sclerosis-progression pattern was also observed. The hybrid pattern of increase of FDG uptake on PET/lytic change on CT is most accurate to show progression of bone metastases. Assessments of these processes during therapy are nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Radionuclide bone scans (bone scintigraphy and SPECT) make use of 99m Technetium ( 99m Tc) diphosphonate as a tracer, which is bone matrix-specific, being the deposit proportional to blood flow and the osteoblastic activity [15]. This tracer identifies the bone reaction to the tumour, but is unable to detect the bone-marrow involvement [16]. As a result, 99m Tc-based imaging does not reliably distinguish between reparative osteoblastic activities (flare) versus (vs) true disease progression.…”
Section: Bone Metastasis Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Radionuclide bone scans (bone scintigraphy and SPECT) make use of 99m Technetium ( 99m Tc) diphosphonate as a tracer, which is bone matrix-specific, being the deposit proportional to blood flow and the osteoblastic activity [15]. This tracer identifies the bone reaction to the tumour, but is unable to detect the bone-marrow involvement [16]. As a result, 99m Tc-based imaging does not reliably distinguish between reparative osteoblastic activities (flare) versus (vs) true disease progression.…”
Section: Bone Metastasis Imagingmentioning
confidence: 99%
“…Morphologic MRI is superior to radiographs or scintigraphy in the assessment of focal lesions, since it allows the detection of bone-marrow replacement by tumour cells before the onset of trabecular changes. Since specificity can be lower to [18] F-FDG PET/CT, MRI studies should not be read isolated, but integrated with other imaging modalities [16]. New functional techniques, such as whole-body diffusion-weighted (DW) or dynamic contrast-enhanced (DCE) MRIs, are beginning to be explored with exciting possibilities [21].…”
Section: Bone Metastasis Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in 23 out of 40 patients, a solitary lesion was detectable. Ultimately, in 2012, a study by Katayama et al proved that change in tumor marker levels is primarily correlated with PET findings than CT, however, the hybrid pattern obtained by combining PET and CT imaging allow an optimal detection of FDG uptake to monitor disease progression, particularly in case of bone metastases, respect to other conventional imaging modalities [62]. …”
Section: Tumor Markers For Surveillance After Primary Bc Treatmentmentioning
confidence: 99%
“…Taking advantage of the metabolic information to interpret the morphological changes is possible with combined PET/CT and increases specificity. It has been reported that progressive breast cancer bone metastases become more lytic and 18F‐FDG‐avid, but increased sclerosis can be associated with response and progression . Whereas reduction in 18F‐FDG uptake in metastases (as measured by the maximum standardized uptake value [SUVmax]) and increased sclerosis on CT has been reported to predict time to progression, only SUVmax remained significant in a multivariate model .…”
Section: Pet and Pet/ctmentioning
confidence: 99%